Psychosocial Stressors and Adaptive Coping Strategies in Couples After a Diagnosis of Young-Onset Dementia. (19th April 2021) - Bannon, Sarah M; Reichman, Mira; Popok, Paula; Grunberg, Victoria A; Traeger, Lara; Gates, Melissa V; Krahn, Erin A; Brandt, Katherine; Quimby, Megan; Wong, Bonnie; Dickerson, Bradford C; Vranceanu, Ana-Maria
Abstract: Background and Objectives: Diagnoses of young-onset dementias (YODs) are devastating for persons with dementia and spousal caregivers yet limited work has examined both partners' perceptions of challenges and coping after diagnosis. This qualitative study investigated the psychosocial stressors and adaptive coping strategies in couples diagnosed with YOD to inform the development of psychosocial support resources. Research Design and Methods: We conducted live video dyadic interviews with couples (persons with YOD and spousal caregivers together; N = 23 couples). We transcribed interviews and coded data based on a hybrid deductive–inductive approach, with the structure of the coding framework informed by the stress and coping framework, and all codes derived from the data. We derived themes and subthemes related to psychosocial stressors and adaptive coping. Results: We identified 5 themes related to psychosocial stressors: the impact of diagnosis, social and family relationships, changing roles and responsibilities, planning for an uncertain future, and couple communication and relationship strain. We identified 7 themes related to adaptive coping strategies: processing emotions and cultivating acceptance, promoting normalcy, efforts to preserve persons with YOD's independence and identity, collaborative and open communication, social support, meaning-making, humor, and positivity, and lifestyle changes and self-care. Discussion and Implications: We replicated several themes regarding stressors and adaptive coping strategies from prior YOD research and identified novel themes and subthemes related to dyadic stressors, sources of couples' relationship strain, and the ways in which couples effectively cope with YOD. Findings inform the development of dyadic interventions to reduce YOD-related distress for both persons with dementia and spousal caregivers.